Doa dalam Perspektif Agama Buddha - Wati, Mila; Poniman, Poniman; Taridi, Taridi (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2022)
Prayer in Buddhism is different from other religions. In Indonesia itself has various religions. Where in every religion there are various ways of praying. Prayer is a request or hope and praise to God, Praying is one of the important aspects in expressing the meaning of life as a whole. In the literature review, the researchers found many meanings of prayer in every religion. The purpose of prayer is objective, done personally in spiritual activities.